Psychometric Evaluation of the Quality of Nursing Care Scale for Children Hospitalized with Acute Respiratory Infection - dewi elizadiani suza (Universitas Airlangga, 2016)
Introduction: Psychometric Evaluation of the quality of nursing care scale is a vital key to improve the quality of nursing care for hospitalized acute respiratory infection (ARI) children in order to decrease morbidity and mortality of ARI children, especially in Indonesia.Methods: Construct validity was identified using the exploratory factor analysis (EFA), contrasted group approach, and reliability.Results: Construct validity: 1) EFA found that the QNCS-HARIC consisted of 37 items with four factor and total variance explained of 42.92% and factor loadings ranged from .30 to .70; 2) contrasted group approach found that the mean scores of the 37 items QNCS-HARIC between two groups were significantly different (t = -22.91; p = .000); and 3) Cronbach’s alpha coefficient of the total 37 item QNCS-HARIC was .93. Cronbach’s alpha coefficients of Factor 1, 2, 3, and 4 of the 37 item QNCS-HARIC were .87, .80, .77, and .76, respectively.Conclusion: Although the 37 items QNCS-HARIC model was acceptable, it was less representative, especially in the socio-cultural dimension of ARI children and family because it consisted of only 3 from 10 items which could not measure the complate dimension of the socio-cultural aspect.